2011
DOI: 10.2478/s11532-011-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

Trace detection of inorganic oxidants using desorption electrospray ionization (DESI) mass spectrometry

Abstract: Abstract:© Versita Sp. z o.o. Received 9 March 2011; Accepted 24 May 2011 Keywords: Perchlorate and chlorate ions • DESI MS • Ambient ionization methods • Oxidants • ExplosivesDesorption electrospray ionization (DESI), an established ambient ionization method in mass spectrometry (MS) for the analysis of organic compounds, is applied here to trace detection of inorganic salts, including inorganic oxidants. In-situ surface analysis of targeted compounds, including nitrogen-, halogen-and sulfur-salts, down to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…ICP, atomic fluorescence spectroscopy, and atomic emission spectroscopy were applied to analyze intact rockets and pyrotechnic fountains, in search of metallic content in the charges . Moreover, desorption ESI with MS was used for the analysis of a preblast rocket, and laser electrospray coupled with MS was utilized for the direct analysis of pre‐ and post‐blast samples from different sorts of surfaces . Additionally, CE with UV‐Vis detection was applied to analyze pre‐ and post‐blast samples of some consumer fireworks .…”
Section: Introductionmentioning
confidence: 99%
“…ICP, atomic fluorescence spectroscopy, and atomic emission spectroscopy were applied to analyze intact rockets and pyrotechnic fountains, in search of metallic content in the charges . Moreover, desorption ESI with MS was used for the analysis of a preblast rocket, and laser electrospray coupled with MS was utilized for the direct analysis of pre‐ and post‐blast samples from different sorts of surfaces . Additionally, CE with UV‐Vis detection was applied to analyze pre‐ and post‐blast samples of some consumer fireworks .…”
Section: Introductionmentioning
confidence: 99%
“…Explosive perchlorate compounds were also of interest in this study because of their widespread use [31]. The direct analysis of 5.0 mg of tetrabutylammonium perchlorate was analyzed in full scan negative ion mode to look for perchlorate ions, as well as in the positive ion mode to measure tetrabutylammonium (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Sokol et al demonstrated trace detection of chlorate, perchlorate, nitrate, and sulfate inorganic oxidizers from surfaces including glass, wood, metal, cotton, filter paper, and PTFE by DESI-MS. 111 Sub-nanogram sensitivities were achieved for sodium chlorate and sodium perchlorate on the majority of non-porous surfaces. 111 Similar to the implementation for peroxide-based explosive detection, Hernandes et al used EASI to detect ANFO (ammonium nitrate-fuel oil) fuel-oxidizer mixtures and rhodamine B-based antitheft device markers directly off of banknotes from simulated and actual ATM explosion thefts (Figure 8). 147 Unique markers from the ANFO were observed in negative mode, specifically, 24 Mg(NO 3 ) 3 − , and confirmed by high resolution ESI-FTMS (Fourier transform mass spectrometry).…”
Section: Inorganic Explosives and Device Componentsmentioning
confidence: 98%
“…107, 108 Similar to a number of classical MS platforms, ambient MS techniques enable the simultaneous or near-simultaneous detection of both organic and inorganic species. 89, 109111 This aspect becomes vital in the consideration of explosives detection, specifically with homemade fuel-oxidizer mixtures and improvised explosive devices.…”
Section: Advances In Ambient Mass Spectrometrymentioning
confidence: 99%